(untitled) (Research, Society and Development, 2021)
Physics teaching, especially in public schools, has always generated discussions related to how content is approached in the classroom. The teaching-learning process of this discipline is the focus of debate because it is seen as something complex and abstract due to the fact that students have difficulties in relating the concepts to their real applications. In order to deconstruct this assumption, this article analyzes the application of a didactic sequence based on the theory of psychologist David Ausubel, whose proposal was implemented in a 2nd year class of integrated technical high school in the Chemistry course at the Federal Institute of Ceará (IFCE). The sequence in question is formed by didactic resources that can mitigate the theoretical abstraction of the content of electrodynamics, of which involve robotics, quizzes, computer simulations and concept maps. The results obtained indicate the potential of the activities carried out in the didactic sequence in the sense of the conceptual evolution of the students’ thinking, regarding the studied concepts. It was possible to perceive, through the use of this methodology, that the students obtained a better understanding of the theme approached, so that it was possible to prove the effectiveness of the experimental practice combined with the other didactic resources involved in the didactic sequence.